SUFFICIENCY AND INSUFFICIENCY OF HOTEL FACILITIES AND SERVICES FOR GUESTS WITH SPECIAL NEEDS: THE CASES OF PORTUGAL AND CYPRUS - Liasidou, Sotiroula; Umbelino, Jorge; Viegas, Cláudia (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
Adequate facilities and appropriate customer service in the hotel industry are needed to cater the increasing numbers of people with special needs, including within the senior cohort. This paper purpose is to assess and compare the cases of Cyprus and Portugal – countries that are highly dependent on the tourism industry – and to identify whether their hotels have the necessary facilities and employees are well equipped to support guests with special needs. The results reveal that both Portuguese and Cypriot hotels regard their facilities as adequate for people with physical disabilities but exclude guests with other types of disabilities. Furthermore, employees are not well prepared to provide services to this cohort of the market. This failure to develop the necessary structures has implications for these countries’ competitiveness in terms of becoming accessible and disabled-friendly destinations.